THE EFFECT OF TUTORING AND CREATIVITY AGAINST STUDENT ACHIEVEMENT OF CLASS XII STUDENTS SMA NEGERI 2 SERANG CITY CIPOCOK JAYA DISTRICT - Asri Yulida (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
This study aimed to determine (1) Effect of tutoring on student achievement, (2) Influence of creativity on student achievement, (3) Effects of tutoring and creativity of student achievement at the same time. The results of the analysis of hypothesis (1) The correlation value of X1 with Y was 0.6341 with the coefficient of determination was 40.21 %, (2) The correlation value of X2 with Y was 0.5981 with the coefficients of determination was 35.77 %, (3) The correlation value of X1 and X2 with Y was 0.7188 with the coefficients of determination was 51.66 %. Thus, H0 is rejected and H1 is accepted or there was influence of tutoring and creativity on student achievement.